1960
DOI: 10.1111/j.1939-0025.1960.tb02088.x
|View full text |Cite
|
Sign up to set email alerts
|

School characteristics of male adolescents who later became schizophrenic.

Abstract: The fo llow-up studies of children seen at the Dallas Child Guidance Clinic (9, 10) produced results of sufficient variance with the consensus of research to warrant discussion later in the paper. 712This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.ment, and Personality Ch aracteristics of Psychotic, Psychoneurotic, Delinquent and Normally Adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Given that differences between the schizophrenic and normal subjects selected at random can be demonstrated on the early life measures, conclusions are drawn concerning the causal nature of the social factors involved. Strain, Cooke, and Apolloni (1976) reviewed six retrospective studies ofthis type in the clinical and psychiatric literature, finding that all but one indicated some type of 494 relationship between schizophrenia and early social problems (Birren, 1944;Bower, Shellhamer, & Daily, 1960;Bowman, 1934;Frazee, 1953;Kasarin & Yeo, 1932;O'Neal & Robins, 1958;Wittman & Steinberg, 1944). Studies reviewed by Gottman, Gonso, and Rasmussen (1975) also showed positive findings relating social variables in early life to later adjustment (Cowen et al, 1973;Kohn & Clausen, 1955;Roff, 1961;Roff et al, 1972;Stengel, 1971).…”
Section: Predictive Validitymentioning
confidence: 84%
“…Given that differences between the schizophrenic and normal subjects selected at random can be demonstrated on the early life measures, conclusions are drawn concerning the causal nature of the social factors involved. Strain, Cooke, and Apolloni (1976) reviewed six retrospective studies ofthis type in the clinical and psychiatric literature, finding that all but one indicated some type of 494 relationship between schizophrenia and early social problems (Birren, 1944;Bower, Shellhamer, & Daily, 1960;Bowman, 1934;Frazee, 1953;Kasarin & Yeo, 1932;O'Neal & Robins, 1958;Wittman & Steinberg, 1944). Studies reviewed by Gottman, Gonso, and Rasmussen (1975) also showed positive findings relating social variables in early life to later adjustment (Cowen et al, 1973;Kohn & Clausen, 1955;Roff, 1961;Roff et al, 1972;Stengel, 1971).…”
Section: Predictive Validitymentioning
confidence: 84%
“…Eight of the remaining 26 studies provided data on samples for which another published study reported more complete or up-to-date data. Table 1 details the basic study descriptors and mean effect sizes for the 18 studies included in our analyses (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). (For the list of excluded studies and the study descriptors [location and design], see the data supplement accompanying the online version of this article.…”
Section: Woodberry Giuliano and Seidmanmentioning
confidence: 99%
“…b More than one effect size per study is included when data were provided separately by test or age of testing. Effect sizes were estimated using Cohen's d: (M 1 +M 2 )/square root ([(n 1 -1)(SD 1 ) 2 +(n 2 -1)(SD 2 ) 2 ]/[n 1 +n 2 -2]), with the following qualifications: the Brewer et al (16) (28), the effect size was estimated from the critical ratio using the same equation provided for Cannon et al [17] and Albee et al [27]). Although Offord (30) reported data from matched pairs, the effect size was calculated using sample means and standard deviations per Dunlap et al (33).…”
mentioning
confidence: 99%
“…This has been most clearly revealed in twin studies, in which the patient is compared with a healthy co-twin (e.g. Kringlen, 1967) and it has also been found in comparisons with healthy siblings (Prout & White, 1956) and with former classmates (Bower, Shellhamer & Daily, 1960). Such traits, often called 'dysthymic' traits, are found in patients with depressive disorders, neurosis and schizophrenia, but probably not in those with psychopathic disorders (Tienari, 1963) or in those who have phases of elevation of mood in addition to their phases of depression (bipolar psychosis: Perris, 1966).…”
Section: Predisposition To Mental Illnessmentioning
confidence: 93%